Transport unplugged: KCCs are regulated through an N‐terminal plug of the ion pathway. (25th May 2021) - Kock Flygaard, Rasmus; Neumann, Caroline; Anthony Lyons, Joseph; Nissen, Poul
Abstract : The ability to regulate transmembrane ion transport in response to various cues is vital to any living cell. In neurons, one key example of critical ion control relates to the extrusion of chloride mediated by the potassium‐chloride‐cotransporters (KCC1‐4). In a recent hallmark study, Chi et␣al (2021) report cryo‐EM structures of human KCC1 and KCC3b, delineating in detail how regulation by phosphorylation inhibits the transport activity. The authors also identify a stabilizing binding site for nucleotides and speculate on its functional role. Abstract : Recent structural work uncovers control mechanisms of human potassium‐chloride‐cotransporters by phosphorylation and nucleotides.